Penguatan Kompetensi Mahasiswa Bimbingan dan Konseling melalui Program Online Sit-In Internasional - M. Aris Rofiqi; Sri Adi Nurhayati; Ike Desi Florina; Sesya Dias Mumpuni; Anin Eka Sulistyawati (Universitas Palangka Raya, 2026)
This study aimed to analyze the contribution of an international online sit-in program to strengthening Guidance and Counseling students’ competencies, particularly professional competence, multicultural competence, and academic engagement. This study employed a descriptive qualitative approach with document analysis supported by simple descriptive quantitative data. The data sources included program reports, activity documentation, Mentimeter materials, Kahoot participation records, and supporting documents from the A Week Online Sit-In at Guidance and Counseling Study Program in 2024. The data were analyzed through document inventory, data reduction, thematic categorization, and source triangulation. The findings show that the online sit-in program provided students with early exposure to counseling practice and professional ethics, broadened their multicultural awareness through cross-cultural interaction, and encouraged academic engagement through Kahoot and Mentimeter. These findings indicate that online sit-in can serve as a flexible and participatory micro-internationalization strategy for Guidance and Counseling learning in the digital era. Future studies are recommended to use mixed-method designs or pre-post assessment to examine the impact of this program more systematically.